Albumin Counteracts Immune-Suppressive Effects of Lipid Mediators in Patients With Advanced Liver Disease - China, Louise; Maini, Alexander; Skene, Simon S.; Shabir, Zainib; Sylvestre, Yvonne; Colas, Romain A.; Ly, Lucy; Becares Salles, Natalia; Belloti, Vittorio; Dalli, Jesmond; Gilroy, Derek W.; O’Brien, Alastair (Clinical gastroenterology and hepatology, 2018)
Patients with acute decompensation and acute-on-chronic liver failure (AD/ACLF) have immune dysfunction, which increases their risk for infections; however, there are no effective treatments to restore their immune function. We investigated whether the potentially immune-restorative effects of albumin are mediated by its effects on prostaglandin E2 (PGE2) and other lipids. We analyzed bloods samples from 45 of 79 patients with AD/ACLF and serum levels of albumin less than 30 g/L for whom infusion of 20% human albumin solution (HAS) increased serum levels of albumin 30 g/L or more in a feasibility study of effects of 20% HAS. Immune function was determined by comparison of macrophage function following addition of plasma samples. We also used samples from 12 healthy individuals. We measured binding of plasma proteins to PGE2 and serum levels of endotoxin (lipopolysaccharide) and cytokines; using 10 patients’ samples, we investigated the effects of PGE2 inhibitors. We performed a comprehensive lipid metabolomic analysis using samples from 10 different patients, before and after HAS administration. At baseline, AD/ACLF patient plasma induced significantly lower production of tumor necrosis factor by healthy macrophages than plasma from healthy individuals (P < .0001). Plasma from patients after HAS infusion induced significantly higher levels of tumor necrosis factor production by macrophages (19.5 ± 4.8 ng/mL) compared with plasma collected before treatment (17.7 ± 4.5 ng/mL; P = .0013). There was a significantly lower proportion of plasma protein (albumin) binding to PGE2 from patients with AD/ACLF plasma (mean, 61.9%) compared with plasma from control subjects (77.1%; P = .0012). AD/ACLF plasma protein binding to PGE2 increased following HAS treatment compared with baseline (mean increase, 8.7%; P < .0001). Circulating levels of PGE2, lipopolysaccharide, and inflammatory or anti-inflammatory cytokines were higher in patients with AD/ACLF than healthy volunteers. Unexpectedly, HAS infusion had no effect on mediator levels. Principal component analysis of baseline levels of lipids that induce or resolve inflammation identified 2 distinct groups of patients that differed according to baseline plasma level of lipopolysaccharide. Sample analyses after HAS treatment indicated that albumin regulates circulating levels of lipid mediators, but this effect was distinct in each group. Analysis of blood samples from patients with AD/ACLF participating in a feasibility study of 20% HAS infusions has shown that infusions to raise serum albumin above 30 g/L reversed plasma-mediated immune dysfunction by binding and inactivating PGE2. We also describe a method to classify the inflammatory response in AD/ACLF, based on lipid profile, which could improve identification of patients most likely to respond to HAS treatment. A randomized controlled trial is needed to determine whether these effects of HAS reduce infections in AD/ACLF. Trial registered with European Medicines Agency (EudraCT 2014-002300-24) and adopted by NIHR (ISRCTN14174793).